Effect of Priming Treatment and Aluminum Stress on Soybean (Glycine max (L.) Merrill) Seeds Viability - Hasanatunnisa, Sahla Sania; Zumani, Darul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Soybean (Glycine max (L.) Merrill) is recognized as one of important functional food that contributes significantly to fulfilling the nutritional and dietary needs of the population. However, efforts to increase soybean production are often hindered by problems faced by the plants on suboptimal land, particularly on acidic soils that can induce aluminum stress. Seed priming has been identified as a method to enhance seed quality, as it can improve seed viability and performance under stress conditions. This study aims to determine the interaction effect between priming treatment and aluminum stress on soybean seeds viability. The research was conducted in January 2025 at the Production Laboratory, Faculty of Agriculture, Siliwangi University. This research use a factorial randomized complete block design (RCBD) with three replications. The first factor was seed priming using four different solutions: distilled water, KNO₃, PEG6000, and GA₃. The second factor was aluminum stress using AlCl36H2O consist levels of four concentrations: 0, 121, 242, and 363 ppm. The results showed that interaction effects occurred on germination percentage and vigor index, while no interaction effect on germination speed, radicle length, shoot length, and seedling dry weight. For germination percentage and vigor index parameters, the effects of priming varied depended on the level of aluminum stress. Priming with PEG6000 and GA₃ showed potential in mitigating aluminum stress in soybean and aluminum stress at 242 ppm can still be tolerated by soybean seeds that primed with GA₃.